A Study and Analysis of Speckle Reduction Method in Digital Holography - Amrutha, C; Manikandan, LC; Akhila, VA (International Journal of Computer Sciences and Engineering, 2025)
Image denoising has become a very essential in the case of noisy images for better information extraction. On the other hand, processed image must reserve the relevant details of the primary image. This noise suppression is very useful in many applications. Speckle noise is one of the major noises causing digital hologram. So we need some mechanism for denoising the noisy content by preserving the valuable information. This paper presents a comparative study on BEMD (bi-dimensional empirical mode decomposition) and MBEMD (multilevel bi-dimensional empirical mode decomposition) along with the frost filter.